If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x/2+x/3=(x+7)/3
We move all terms to the left:
x/2+x/3-((x+7)/3)=0
We calculate fractions
27x^2/()+2x/()+(-((x+7)*2)/()=0
We calculate terms in parentheses: +(-((x+7)*2)/(), so:We get rid of parentheses
-((x+7)*2)/(
We multiply all the terms by the denominator
-((x+7)*2)
We calculate terms in parentheses: -((x+7)*2), so:We get rid of parentheses
(x+7)*2
We multiply parentheses
2x+14
Back to the equation:
-(2x+14)
-2x-14
Back to the equation:
+(-2x-14)
27x^2/()+2x/()-2x-14=0
We multiply all the terms by the denominator
27x^2+2x-2x*()-14*()=0
We add all the numbers together, and all the variables
27x^2+2x-2x*()=0
| (1/4)b-5=3 | | 6f÷7=49 | | 4+f=f | | 3(4^x/2)=96 | | 2/x+5/2x=9 | | 3+7x=60 | | 14/12x+22/10x=x | | (y+10+3y-2)=180 | | 3x+3=67+12 | | 4h÷1=21 | | (x+7)2-49=0 | | 16x+31-13x+11=82 | | 70-7b=9b | | 10u=100,000 | | (250+x)+x=1000 | | 12-2a=7a-15 | | 9^x=47 | | u=24/5 | | X^2+17x+25=0 | | 17+3y=50 | | 2f–5=1 | | 6Xc=53+8+12 | | 192=-8p+8(6p-6) | | (6n+5)/(2n^2=3n) | | 3x+3x=16+8x | | 5z-1=3 | | 7+7x=13+9x | | 6x/5-7=5 | | 8(3x+2)=12x-4 | | X/3+3=x-7 | | 3.6(z=2.6)=54 | | u^2-3u+6=0 |